Award for 2nd best e-poster of the Greek Psychiatric Association, 31st Annual Greek National Psychiatric Conference - Karanikola, Maria (My University, 2026)
Award for 2nd best e-poster under the title "Effectiveness of an educational intervention on enhancement of ill health self-management skills in adults diagnosed with bipolar disorder: Results of the ΜοΒ(Management Of My Bipolarity) study"
Keywords: Sciences